2022
DOI: 10.1002/rth2.12699
|View full text |Cite
|
Sign up to set email alerts
|

Reversing direct factor Xa or thrombin inhibitors: Factor V addition to prothrombin complex concentrate is beneficial in vitro

Abstract: Background Prothrombin complex concentrate (PCC) is a human plasma‐derived mixture of partially purified vitamin K‐dependent coagulation factors (VKCF). Current therapeutic indication is treatment and perioperative prophylaxis of bleeding in acquired VKCF deficiency. Off‐label uses include treatment of direct factor Xa‐ or thrombin inhibitor‐associated bleeds, treatment of trauma‐induced coagulopathy, and hemorrhagic complications in patients with liver disease. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
3
2
0
Order By: Relevance
“…APIX reduced platelet and fibrin interactions with the thrombogenic surface exposed to circulating blood. Inhibition in platelets and fibrin formation has been reported for different DOACs in previous studies from our group and others 20 , 21 , 28 , 29 . Interestingly, one of the previous studies reported a delayed fibrin formation in DOAC-treated under static conditions 29 .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…APIX reduced platelet and fibrin interactions with the thrombogenic surface exposed to circulating blood. Inhibition in platelets and fibrin formation has been reported for different DOACs in previous studies from our group and others 20 , 21 , 28 , 29 . Interestingly, one of the previous studies reported a delayed fibrin formation in DOAC-treated under static conditions 29 .…”
Section: Discussionsupporting
confidence: 78%
“…Inhibition in platelets and fibrin formation has been reported for different DOACs in previous studies from our group and others 20 , 21 , 28 , 29 . Interestingly, one of the previous studies reported a delayed fibrin formation in DOAC-treated under static conditions 29 . Our present microfluidic studies with recalcified anticoagulated blood were performed for a relatively short time (3 min) to avoid clotting of the system.…”
Section: Discussionsupporting
confidence: 78%
“…APIX reduced platelet and fibrin interactions with the thrombogenic surface exposed to circulating blood. Inhibition in platelets and fibrin formation has been reported for different DOACs in previous studies from our group and others [27,28,32,33]. Interestingly, one of the previous studies reported a delayed fibrin formation in DOAC-treated under static conditions [33].…”
Section: Discussionsupporting
confidence: 60%
“…Inhibition in platelets and fibrin formation has been reported for different DOACs in previous studies from our group and others [27,28,32,33]. Interestingly, one of the previous studies reported a delayed fibrin formation in DOAC-treated under static conditions [33]. Our present microfluidic studies with recalcified anticoagulated blood were performed for a relatively short time (3 min) to avoid clotting of the system.…”
Section: Discussionmentioning
confidence: 66%
“…There are four-factor (4F-PCC), three-factor (3F-PCC) and activated PCC formulations [60,61]. The key differentiator is the inclusion of factor VII in 4F-PCC, believed to enhance hemostatic efficacy compared to 3F-PCC [62,63]. Activated PCC contains nonactivated factors II, IX, and X as well as activated factor VII.…”
Section: Prothrombin Complex Concentratesmentioning
confidence: 99%